Preferred reporting items for studies mapping onto preference-based outcome measures: the MAPS statement - Petrou, S; Rivero-Arias, O; Dakin, H; Longworth, L; Oppe, M; Froud, R; Gray, A (Cambridge University Press, 2015)
"Mapping" onto generic preference-based outcome measures is increasingly being used as a means of generating health utilities for use within health economic evaluations. Despite publication of technical guides for the conduct of mapping research, guidance for the reporting of mapping studies is currently lacking. The MAPS (MApping onto Preference-based measures reporting Standards) statement is a new checklist, which aims to promote complete and transparent reporting of mapping studies.In the absence of previously published reporting checklists or reporting guidance documents, a de novo list of reporting items was created by a working group comprised of six health economists and one Delphi methodologist. A two-round, modified Delphi survey with representatives from academia, consultancy, health technology assessment agencies, and the biomedical journal editorial community was used to identify a list of essential reporting items from this larger list.From the initial de novo list of twenty-nine candidate items, a set of twenty-three essential reporting items was developed. The items are presented numerically and categorized within six sections, namely: (i) title and abstract, (ii) introduction, (iii) methods, (iv) results, (v) discussion, and (vi) other. The MAPS statement is best applied in conjunction with the accompanying MAPS explanation and elaboration document.It is anticipated that the MAPS statement will improve the clarity, transparency. and completeness of reporting of mapping studies. To facilitate dissemination and uptake, the MAPS statement is being co-published by seven health economics and quality of life journals, and broader endorsement is encouraged. The MAPS working group plans to assess the need for an update of the reporting checklist in five years' time.